Pelajaran Bahasa Indonesia dalam Perspektif Berbagai Kurikulum : Studi Komprehensif dengan Pendekatan Teoritis - Much Nuril Huda (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study analyzes the development of the Indonesian Language curriculum from time to time with a focus on three main curricula: KTSP (2006), Curriculum 2013, and Merdeka Curriculum (2022). Through a qualitative approach and literature study, this study examines the differences in philosophy, structure, learning methods, and evaluation systems in the three curricula. The analysis is enriched with various educational theories to provide a comprehensive understanding. The results of the study indicate an evolution from a behavioristic approach to a constructivist one, with Merdeka Curriculum offering the most holistic solution to the challenges of 21st century education.